Sedimentary Facies Evaluation of Tight Oil Reservoirs of Yanchang Formation in the Ordos Basin - Yu Peng; Huaijie Zhang; Xiaoli Zheng; Yi Wang; Jiye Li; Yinhui Zhu; Quine Doolen (Journal of Chemistry)
Tight sandstone gas has become one of the important unconventional resources. It is of great significance to study the pore throat structure of tight sandstone for the development of tight sandstone gas reservoirs. On the basis of previous research results, this paper studies the tight reservoir characteristics of Yanchang Formation by combining geological data with geophysical logging. The reservoir characteristics are described and studied in detail by ordinary thin section, casting thin section, graphic granularity, and scanning electron microscope experiment. The experimental results show that the reservoir sandstone types of long 6 segments are mainly lithic feldspathic sandstone and feldspathic lithic sandstone, with high component maturity and structural maturity. The components of cement mainly include authigenic clay minerals illite, chlorite, and carbonate minerals. The reservoir space is mainly composed of feldspar-dissolved pores and residual intergranular pores. Compaction and cementation are the decisive factors of pore reduction. At present, the average porosity of the reservoir is 8.33% and the average permeability is 0.12 × 10−3 μm2, which belong to an ultralow porosity and ultralow permeability reservoir. On the basis of studying the origin, superimposition, and distribution of sand bodies and taking into account the sedimentary characteristics, origin, and trigger mechanism of gravity flow, a multisource sedimentary model is established in the study area, which is dominated by sandy debris flow, accompanied by turbidity current and local development of sandy slump. The thick massive sandstone with the most exploration significance in the study area is formed by the superimposition of multistage sandy clastic flow sediments along the gully in the direction of delta to lake. Summarizing the characteristics of reservoir development and evaluating and predicting it can provide geological basis for the next exploration and development of deep-water tight reservoirs in the study area.